Fundamental Analysis of Stocks Before and After the COVID-19 Pandemic on the Indonesia Stock Exchange (An Empirical Study of the IDX30 Index) - Jayati, Arum; Zein, Pasti Yohana; Jihan, Perina Rama (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2023)
The purpose of this study is to analyze the performance of stocks listed in the IDX30 index on the Indonesia Stock Exchange before and after the COVID-19 pandemic, covering the period from 2017 to 2021, using fundamental analysis. This analysis aims to determine whether stock performance during this period was beneficial or detrimental to investors. The study focuses on key fundamental indicators, including Earnings Per Share (EPS), Price to Earnings Ratio (PER), Debt to Equity Ratio (DER), Return on Assets (ROA), and Return on Equity (ROE). Using purposive sampling, the study selected 15 companies that were consistently listed in the IDX30 index throughout the 2017–2021 period.